Reliability of Odontometric Variations as an Important Aid in Gender Determination (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Introduction: Determination of gender of human remains in forensic context constitutes an important and essential step in medico-legal examination. The ability of the calcified and inert structures of teeth to resist post-mortem degradation and to survive natural or accidental change has led forensic science experts to focus on the teeth as a possible source for valuable forensic data in poorly preserved human remains. Gender variations in human dentition have been of great help for both forensic odontologists and anthropologists. Assessment of gender from tooth measurements acts as a useful adjunct to identify forensic specimens, as the sizes of teeth show differences between gender of an individual and among different populations. Objectives: The present study aims to determine gender of an individual based on buccolingual, mesiodistal and cervicoincisal dimensions of teeth and analyse if any sexual variations existed in any of the dimensions of maxillary and mandibular teeth except third molars. Materials and methods: The study examined 110 individuals which included 55 males and 55 females in the age group of 18–24 years. Buccolingual, mesiodistal and cervicoincisal dimensions of teeth were measured using digital vernier calliper (.01-mm calibration). Using SPSS version 20, independent t test and stepwise discriminant analysis were applied to the significant mean value and reliability of tooth dimensions. Results: Buccolingual, mesiodistal and cervicoincisal dimensions were larger in males than females. The difference between the means of all the three tooth dimensions in both arches between males and females was statistically significant. All the three different dimensions are independent of each other. There is no relation between the dimensions. Conclusion: Both the arches were studied, and all the three dimensions were evaluated. All the three dimensions were larger in males than females for both the arches. Reliability of buccolingual dimension was found to be more than other dimensions for both the arches of both genders. Mesiodistal and cervicoincisal dimensions were reliable only for maxillary teeth of both the genders.
Keywords: Buccolingual; Mesiodistal; Cervicoincisal; Odontometric; Gender; Tooth; Dimensions